The relationship between albumin-corrected anion gap and hyperuricemia and its role in cardiovascular risk assessment: mediation effect analysis of triglycerides and non-high-density lipoproteins - Yan, Manli; Shi, Wenhua; Zhang, Kaiyuan; Gong, Ping; Wei, Hua; Li, Xiang (Frontiers in Endocrinology, 2025)
BackgroundThis study examines the relationship between Albumin-Corrected Anion Gap (ACAG) and hyperuricemia (HUA), as well as its potential mechanisms linking HUA to cardiovascular diseases. While HUA is associated with cardiovascular conditions, whether it is an independent risk factor remains unclear. ACAG, an indicator of acid-base balance, has prognostic value in cardiovascular outcomes, but its relationship with HUA has not been explored.MethodsData from 4,588 adults who visited Guangdong Provincial Hospital of Chinese Medicine between January and December 2023 were analyzed. HUA was defined as a serum uric acid (SUA) level >420 μmol/L, with the remaining participants categorized as Non-HUA. SPSS, R, and “Zstats” software were used for data analysis.ResultsOf the participants, 1,135 (24.7%) were in the HUA group, with 86.4% males. The ACAG, triglycerides (TG) and non-high-density lipoprotein cholesterol (non-HDL-C) levels in the HUA group were significantly higher than those in the Non-HUA group, while HDL-C levels were significantly lower. ACAG was positively correlated with SUA, even after adjusting for age and gender. Non-linear analysis showed that when ACAG exceeded 12.64, each additional unit increase was associated with a 12% increase in the adjusted odds ratio for HUA. Mediation analysis revealed that TG and non-HDL-C partially mediated the association between ACAG and HUA, accounting for 28.3% and 13.5%, respectively.ConclusionThis is the first study to demonstrate a significant correlation between ACAG and HUA, with TG and non-HDL-C acting as mediators, providing new directions for prevention and intervention of HUA.